Diabetes and diabetic retinopathy in people aged 50 years and older in the Republic of Suriname. Issue 6 (20th October 2015) - Minderhoud, Janna; Pawiroredjo, Jerrel C; Bueno de Mesquita-Voigt, Anne-Marie T; Themen, Herman CI; Siban, Michael R; Forster-Pawiroredjo, Cindy M; Limburg, Hans; van Nispen, Ruth MA; Mans, Dennis RA; Moll, Annette C
Abstract : Background/Aims: Population-based surveys on diabetes and diabetic retinopathy (DR) are necessary to increase awareness and develop screening and therapeutic programmes. The aim was to estimate the prevalence of DR in older adults of different ethnic backgrounds in Suriname. Methods: Fifty clusters of 60 people aged ≥50 years were randomly selected with a probability proportional to the size of the population unit. Eligible people were randomly selected through compact segment sampling and examined using the Rapid Assessment of Avoidable Blindness plus Diabetic Retinopathy (RAAB + DR) protocol. Participants were classified as having diabetes if they: were previously diagnosed with diabetes; were receiving treatment for glucose control; had a random blood glucose level >200 mg/dL. These participants were dilated for funduscopy, assessed for DR following the Scottish DR grading protocol and evaluated for ethnicity and DR ophthalmic screening frequencies. Results: A total of 2806 individuals was examined (response 93.6%). The prevalence of diabetes was 24.6%. In these patients any type of DR and/or maculopathy occurred in 21.6% and sight-threatening DR in 8.0%. Of the known diabetics, 34.2% never had an eye examination for DR and in 13.0% the last examination was >24 months ago. The prevalence of diabetes was significantly higher in Hindustani people compared with other major ethnic groups. Conclusions: The prevalence of diabetes and diabetics without regular DR control in people aged ≥50 years in Suriname was higher than expected. The uptake for special services for DR has to be expanded to decrease patient delay and DR-induced blindness.